Risk Factors for Orbital Complication in Odontogenic Rhinosinusitis - Anna Mailasari Kusuma Dewi; Nourma Wahyu Andriani; Desy Iriani (RSUP Dr. Kariadi, 2024)
Background: Orbital involvement is the most common complication in rhinosinusitis presenting about 60-75%. The manifestation of orbital complications such as eyelid edema, proptosis, eye movement disorder and loss of vision. The potential risk factors for developing complications are described in several studies. Purpose: To examine the risk factors for orbital complication in odontogenic rhinosinusitis. Methods: A retrospective case control study of 34 patients from July 2022 to July 2023 based on medical records. The subjects were classified into two groups, the case group involving odontogenic rhinosinusitis patients with orbital complication and the control group involving patients without orbital complications. Risk factors were sex, onset of odontogenic sinusitis, sinonasal symptoms, diabetes, histopathological findings, laboratory findings and CT scan images of sinus. The characteristics of orbital complications and the types of pathogenic bacteria cultivated were recorded. Results: There number of patients in each group were 17, with the female to male ratio of 2,4:1, aged 8 to 81 years were enrolled in this study. The most common orbital complication was sub periosteal abscess (41%). We found 64% positive bacterial growth from tissue culture dominated by Staphylococcus sp. (54.5%). Histopathological examination showed the main inflammatory cell of the sinus mucosal epithelium was neutrophil in both groups. The logistic regression test showed that the risk factors for orbital complication were absolute neutrophil count p 0.008, OR 81.062, mucopurulent discharge p 0.009, OR 0.006 and sinus involvement p 0.027, OR 0.152. Conclusion: Orbital complications were associated with sinus involvement with main symptom involving mucopurulent discharge and higher absolute neutrophil count.